PENGEMBANGAN MODUL MATA KULIAH DESAIN KOMUNIKASI VISUAL I BERBASIS MEDIA DI PROGRAM STUDI DESAIN KOMUNIKASI VISUAL: Media-based Development of Visual Communication Design I Subject Module in the Visual Communication Study Program - Hendro Aryanto; Eko Agus Basuki Oemar (Jurnal Dimensi Seni Rupa dan Desain, 2024)
The learning process in Visual Communication Design I has not been supported by pre-requisite courses that focus on visual communication problems. So that students in the learning process require longer adaptation to master the theory and practice of work. One of the visible symptoms is that the design work designed by students displays aesthetic functions more dominant than their communication functions. Based on this, it is necessary to support teaching materials in the form of modules as an effective and efficient learning medium that can motivate students to learn more independently as well as be creative and innovative in designing visual communication design works. Module development is carried out by research methods using a development model by adapting from the stages of the Four-D Model referenced from Thiagarajan (1974). The development model was later modified into 5-D. Data collection techniques through interviews, observation and documentation. Making modules based on criteria or principles that show the characteristics of a good module, which includes: self instructional, self contained, independent, self assessed, and user friendly. The module development process goes through the stages of needs analysis, determination of concept maps, formats and writing systematics, followed by making modules consisting of four module units. After that, validation is carried out to determine the feasibility of the module as a development product. Then a revision is carried out whose results can be directly used as a learning medium in the module trial stage. The responses of graphic design lecturers and students show that in essence, the modules developed are suitable to be used to support learning about visual language. Besides being able to be used for independent learning in visual communication design lectures, it can also be used for material enrichment in learning Graphic Design or Visual Communication Design.